Measurement invariance and validity of the athlete engagement questionnaire - De Francisco, C.; Arce, C.; Grana, M.; Sanchez-Romero, E. I. (International Journal of Sports Science & Coaching, 2018)
Engagement is a psychological construct that was originally defined in an organizational context to refer to the emotional, cognitive and physical components that drive people to get actively involved in their occupational duties. In sports science, the Athlete Engagement Questionnaire conceptualizes engagement as a multidimensional construct comprising four factors: confidence, vigor, dedication and enthusiasm. The purpose of this study was to analyze the measurement model invariance of the Athlete Engagement Questionnaire across different competitive levels and to provide evidence of construct validity in relation to burnout. To this end, we recruited 1157 athletes of both sexes, aged between 12 and 35 years, to complete the Athlete Engagement Questionnaire and Athlete Burnout Questionnaire. The results provided evidence of Athlete Engagement Questionnaire measurement model invariance and its validity with respect to burnout.